PENGARUH KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA KELAS VII MTS FISABILILLAH - Farah Sadidah Achmad; Fauzi Mulyatna (Program Studi Pendidikan Matematika FIP UNHASY, 2021)
The purpose of this study was to determine how much influence emotional intelligence had on the ability to understand mathematical concepts of grade VII A and VII B students at MTs Fisabilillah School. The instrument in this study used an essay test of five questions and an emotional intelligence questionnaire of 40 statements. Based on the data that has been obtained from the calculation of the effect of emotional intelligence on the ability to understand mathematical concepts of MTs Fisabilillah School students, the researchers can conclude several things including, there is a significant influence on the influence of emotional intelligence on the ability to understand mathematical concepts of MTs Fisabilillah School students of 0.8359 or 69,87%. The rest is influenced by other factors, such as students' thinking ability, and other aspects not examined by this study. This is also reinforced by the results of hypothesis testing which shows that thitung > ttabel is thitung 11.1778 > ttabel= 2.00488 which states that there is a significant influence between emotional intelligence and the ability to understand mathematical concepts.